2007
DOI: 10.1093/molbev/msm158
|View full text |Cite
|
Sign up to set email alerts
|

Divergence in Expression between Duplicated Genes in Arabidopsis

Abstract: New genes may arise through tandem duplication, dispersed small-scale duplication, and polyploidy, and patterns of divergence between duplicated genes may vary among these classes. We have examined patterns of gene expression and coding sequence divergence between duplicated genes in Arabidopsis thaliana. Due to the simultaneous origin of polyploidy-derived gene pairs, we can compare covariation in the rates of expression divergence and sequence divergence within this group. Among tandem and dispersed duplicat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

17
198
0

Year Published

2008
2008
2016
2016

Publication Types

Select...
6
2
2

Relationship

0
10

Authors

Journals

citations
Cited by 226 publications
(215 citation statements)
references
References 72 publications
17
198
0
Order By: Relevance
“…First, each of the three paralogous gene sets exhibit evidence of unequal (or asymmetrical) divergence (Wagner, 2002;Ganko et al, 2007) with respect to the root epidermal network because mutants of one member (cpc, gl3, and wer) have a generally greater impact on downstream gene expression than mutants of the other (try, egl3, and myb23), consistent with their morphological effects. Furthermore, we conclude that, among these three paralogous gene sets, the TRY-CPC set appears to have undergone the least diversification and MYB23-WER the most (with respect to the root epidermal network) because (1) TRY-CPC has the smallest frequency (and MYB23-WER the greatest frequency) of target genes exhibiting high sensitivity to the loss of either member (i. e., number of "H" category genes in each set: TRY-CPC …”
Section: Discussion Molecular Dissection Of Duplicate Gene Functionmentioning
confidence: 87%
“…First, each of the three paralogous gene sets exhibit evidence of unequal (or asymmetrical) divergence (Wagner, 2002;Ganko et al, 2007) with respect to the root epidermal network because mutants of one member (cpc, gl3, and wer) have a generally greater impact on downstream gene expression than mutants of the other (try, egl3, and myb23), consistent with their morphological effects. Furthermore, we conclude that, among these three paralogous gene sets, the TRY-CPC set appears to have undergone the least diversification and MYB23-WER the most (with respect to the root epidermal network) because (1) TRY-CPC has the smallest frequency (and MYB23-WER the greatest frequency) of target genes exhibiting high sensitivity to the loss of either member (i. e., number of "H" category genes in each set: TRY-CPC …”
Section: Discussion Molecular Dissection Of Duplicate Gene Functionmentioning
confidence: 87%
“…Asymmetric expression pattern was also observed between paralogs in Arabidopsis and rice (Blanc and Wolfe, 2004;Ganko et al, 2007;Throude et al, 2009) and between homoeologs in cotton (Chaudhary et al, 2009). Our expression results showed evidence for transcriptional divergence among different tissue types of some homoeolog pairs, consistent with findings in other plant species.…”
Section: Expression Biases Are Correlated With Sequence Divergencementioning
confidence: 77%
“…Previous studies comparing gene expression levels of duplicate genes revealed that expression divergence between copies occurs rapidly (31)(32)(33)(34)(35)(36)(37)(38) and can be asymmetric (32,35,38). However, our analysis is unique in that it uses expression data and phylogenetic relationships among genes to explicitly classify the evolutionary processes underlying the retention of duplicates on a genome-wide scale.…”
Section: Discussionmentioning
confidence: 99%